Pengetahuan Personal Hygiene Remaja Putri pada Kasus Keputihan - Helmy Ilmiawati; Kuntoro Kuntoro (Universitas Airlangga, 2016)
This study was a cross sectional study. This research was conducted at the Institute of Islamic Education Nurul Haromain “SMP Plus Fityani